Research on Feedback in Spanish: A Systematic Review of the Literature; [Pesquisa Sobre Feedback Em Espanhol: Uma Revisão Sistemática Da Literatura]; [Investigación Sobre Retroalimentación en Español: Una Revisión Sistemática de la Literatura] - Herrera-Araya, D (Fundacao Cesgranrio, 2023)
The purpose of this article is to analyze the empirical research on feedback in Spanish. Using a systematic literature review methodology, 20 studies were selected from a total of 297 articles published between 2007 and 2021. The results of the review indicate that there is: a) a predominance of studies in higher education, b) a restricted development of theoretical frameworks for the problematization of feedback and c) poorly formulated methodological approaches and designs, which affects a limited analysis and discussion of results. It is concluded that research on feedback in Spanish is a field under construction, peripheral to international debates and productions, so it is necessary to make systematic efforts to strengthen its research contribution in the field. © 2023 Fundacao Cesgranrio. All rights reserved.